Whose city now? Urban managerialism reconsidered (again). Issue 2 (May 2017) - Forrest, Ray; Wissink, Bart
This introductory essay reflects on the continuing relevance of Ray Pahl's Whose City? It reassesses the original urban managerialist perspective, developed in the Europe of the late 1960s and early 1970s. When large-scale public institutions dominated access to scarce urban resources, Pahl argued that urban managers played a crucial role in the shaping of life chances. But with the emergence of Marxist perspectives on the city under capitalism, urban managers receded from view as minor players within overarching structures of exploitation and inequality. This was only reinforced by the neoliberal transformations that started to take hold after the late 1970s. We are now living in a very different world of global financialized capitalism in which the relevance of various radical theorists is being reassessed. Have new urban managers emerged? Who are they and what do they do? Should we modify the urban managerialist perspective for the post-privatized city, the city of 'governance', the city of choice in which interests and responsibilities appear to have become more fragmented and less transparent? The essay concludes with a discussion of the other papers in this special section and their contribution to a reassessment of Ray Pahl's urban managerialism.